Evaluating bowel enterotomy closures in simulated deep body cavities using the reversing half-hitch alternating post and square knots: a randomized controlled trial - Sykes, Edward A. (Can J Surg, 2021)
BACKGROUND: Square knots can be difficult to construct in deep body cavities. The reversing half-hitch alternating post (RHAP) surgical knot has noninferior tensile strength and performance characteristics in deep body cavities. We compared the enterotomy repairs of novice learners in simulated deep body cavities using RHAP versus square knots after proficiency-based training. METHODS: Undergraduate students were randomized to RHAP (n = 10) or square knot (n = 10) groups and trained to defined proficiency. They then performed hand-sewn enterotomy repairs of cadaveric porcine small bowels on flat surfaces and in simulated deep body cavities. We recorded time to knot-tying proficiency and to enterotomy repair, and burst pressures for the repair. RESULTS: Mean time-to-proficiency in knot tying was equivalent between the RHAP and square knot groups (23 [standard deviation (SD) 3] v. 21 [SD 2] min, p = 0.33). Mean time for enterotomy repair in deep cavities was shorter for the RHAP group (16 [SD 2] min v. 21 [SD 1] min, p = 0.02). Mean burst pressures for enterotomy repair were equivalent on flat surfaces (128 [SD 41] v. 101 [SD 36] mm Hg, p = 0.31), and were significantly higher for the RHAP group in simulated deep body cavities (32 [SD 13] v. 105 [SD 37] mm Hg, p = 0.05). CONCLUSION: The RHAP knots appear to have superior performance versus square knots when tied in a deep body cavity by novice learners. Future work should focus on demonstrating the clinical relevance and broad utility of the RHAP knot in abdominal surgery. Both knot types should be taught to novice learners.